Involvement of Raft-Like Plasma Membrane Domains of Entamoeba histolytica in Pinocytosis and Adhesion - Laughlin, Richard C. (American Society for Microbiology, 2004)
Lipid rafts are highly ordered, cholesterol-rich, and detergent-resistant microdomains found in the plasma membrane of many eukaryotic cells. These domains play important roles in endocytosis, secretion, and adhesion in a variety of cell types. The parasitic protozoan Entamoeba histolytica, the causative agent of amoebic dysentery, was determined to have raft-like plasma membrane domains by use of fluorescent lipid analogs that specifically partition into raft and nonraft regions of the membrane. Disruption of raft-like membrane domains in Entamoeba with the cholesterol-binding agents filipin and methyl-β-cyclodextrin resulted in the inhibition of several important virulence functions, fluid-phase pinocytosis, and adhesion to host cell monolayers. However, disruption of raft-like domains did not inhibit constitutive secretion of cysteine proteases, another important virulence function of Entamoeba. Flotation of the cold Triton X-100-insoluble portion of membranes on sucrose gradients revealed that the heavy, intermediate, and light subunits of the galactose-N-acetylgalactosamine-inhibitible lectin, an important cell surface adhesion molecule of Entamoeba, were enriched in cholesterol-rich (raft-like) fractions, whereas EhCP5, another cell surface molecule, was not enriched in these fractions. The subunits of the lectin were also observed in high-density, actin-rich fractions of the sucrose gradient. Together, these data suggest that pinocytosis and adhesion are raft-dependent functions in this pathogen. This is the first report describing the existence and physiological relevance of raft-like membrane domains in E. histolytica.